Development of 3D heteroatom-doped graphene oxide composites for removing tricyclic antidepressant pharmaceutical residues from wastewater - Tee, Wan Ting (2025)
Tricyclic antidepressant (TCA) residues in water sources are an emerging environmental concern due to increasing usage and potential risks to ecosystems and human health. Their persistence and biological activity have led to recent frequent detection in aquatic environments. However, conventional wastewater treatment processes are not designed to effectively remove such emerging contaminants. Heteroatom doping of graphene has shown potential in enhancing adsorption performance for various water pollutants, but its application for TCA removal remains underexplored. This thesis addresses this research gap by developing novel three-dimensional (3D) heteroatom-doped graphene oxide (GO) composites for efficient TCAs adsorption from aqueous solutions.